2018
DOI: 10.1186/s40645-018-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

Paleoceanographic history of the Japan Sea over the last 9.5 million years inferred from radiolarian assemblages (IODP Expedition 346 Sites U1425 and U1430)

Abstract: Previous studies showed that the evolution of the Japan Sea paleoceanography since the Miocene has been influenced by the regional tectonism (e.g., opening/closing of the connecting seaways) and regional/global climate. In the Japan Sea, Expedition 346 of the Integrated Ocean Drilling Program (IODP) retrieved core sediments dating back to the Miocene at two sites (U1425 and U1430). In this study, we reconstruct shallow-to-deep-water hydrography of the Japan Sea during the Mio-Pliocene based on radiolarian asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 116 publications
(281 reference statements)
1
43
0
Order By: Relevance
“…We integrate several age models for Site U1430 (Kamikuri et al 2017;Matsuzaki et al 2018;Kurokawa et al 2019) that are of similar sampling resolution and cover the same age range as our study. We therefore use these models rather than, for example, a higherresolution age model for only the youngest 1 Ma (Tada et al 2018).…”
Section: Site Setting Sample Selection and Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…We integrate several age models for Site U1430 (Kamikuri et al 2017;Matsuzaki et al 2018;Kurokawa et al 2019) that are of similar sampling resolution and cover the same age range as our study. We therefore use these models rather than, for example, a higherresolution age model for only the youngest 1 Ma (Tada et al 2018).…”
Section: Site Setting Sample Selection and Stratigraphymentioning
confidence: 99%
“…We therefore use these models rather than, for example, a higherresolution age model for only the youngest 1 Ma (Tada et al 2018). Matsuzaki et al (2018) identified a hiatus between c. 4 Ma and 7.3 Ma. Bulk accumulation rates (BAR; g cm −2 ka −1 ) for individual samples were calculated from the dry bulk density and linear sedimentation rates.…”
Section: Site Setting Sample Selection and Stratigraphymentioning
confidence: 99%
“…The microfossil group of radiolarians is the only abundant group bearing skeletons composed of amorphous silica (SiO 2 •nH 2 O) and inhabiting deep to shallow water depths (e.g., Suzuki and Aita 2011;Suzuki and Not 2015). Numerous studies of radiolarians in the Northwest Pacific and its adjacent marginal seas have demonstrated the suitability of this microfossil group as a paleoceanographic proxy (e.g., Itaki et al 2007Itaki et al , 2009Kamikuri et al 2007;Matsuzaki et al 2014aMatsuzaki et al , 2018Okazaki et al 2004). Recently, Integrated Ocean Drilling Program (IODP) Expedition 346, which aimed to reconstruct changes in EASM intensity since the Pliocene at high resolution, retrieved sediment cores at Site U1429 in the Danjo Basin of the northern ECS.…”
Section: Introductionmentioning
confidence: 99%
“….45 Ma were too low (~1 cm/kyr) to detect meaningful orbital-scale changes in GRA, and the radiolarian datums and the occurrence of a glauconite layer suggest a hiatus during the time interval from 7 to 5 Ma (Kamikuri et al 2017;Matsuzaki et al 2018;Tada et al 2015c). For this reason, we conducted an orbital tuning only for 11.8 to 7.3 Ma.…”
Section: Chronologymentioning
confidence: 99%
“…The presence of parallel laminations only at site U1425 in the upper part of unit IIIA signifies euxinic or anoxic conditions in the bottom water there and oxic or suboxic conditions at site U1430, whereas the presence of parallel laminations only at site U1430 in the lower part of unit IIIA (~9.0 Ma) may indicate the development of an oxygen minimum zone within the Japan Sea, because site U1430 was at the appropriate paleo-water depth. Another line of evidence that an oxygen minimum zone developed or expanded in the Japan Sea around 8 Ma is radiolarian data indicating the presence of North Pacific type deep-water species at that paleo-water depth (Matsuzaki et al 2018).…”
Section: Lithostratigraphic Correlation Of Japan Sea Sites and Refinementioning
confidence: 99%